2019
DOI: 10.1103/physreva.100.033819
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth and conversion efficiency analysis of dissipative Kerr soliton frequency combs based on bifurcation theory

Abstract: Dissipative Kerr soliton frequency combs generated in high-Q microresonators may unlock novel perspectives in a variety of applications and crucially rely on quantitative models for systematic device design. Here, we present a global bifurcation study of the Lugiato-Lefever equation which describes Kerr comb formation. Our study allows systematic investigation of stationary comb states over a wide range of technically relevant parameters. Quantifying key performance parameters of bright and dark-soliton combs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The formation of LSs in the normal regime has been addressed in a number of theoretical works (Godey et al, 2014b;Lobanov et al, 2015;Parra-Rivas et al, 2016a,b;Gärtner et al, 2019), and their existence has been confirmed experimentally in microresonators (Xue et al, 2015;Nazemosadat et al, 2019) and pulse-pumped fiber cavities (Garbin et al, 2017). In this section we present the main results regarding the origin and bifurcation structure of dark LSs in this regime of operation.…”
Section: Localized Structures In the Normal Regime: Collapsed Snakingmentioning
confidence: 78%
See 1 more Smart Citation
“…The formation of LSs in the normal regime has been addressed in a number of theoretical works (Godey et al, 2014b;Lobanov et al, 2015;Parra-Rivas et al, 2016a,b;Gärtner et al, 2019), and their existence has been confirmed experimentally in microresonators (Xue et al, 2015;Nazemosadat et al, 2019) and pulse-pumped fiber cavities (Garbin et al, 2017). In this section we present the main results regarding the origin and bifurcation structure of dark LSs in this regime of operation.…”
Section: Localized Structures In the Normal Regime: Collapsed Snakingmentioning
confidence: 78%
“…Unlike HH the subsidiary primary bifurcations cannot be characterized in terms of spatial dynamics. However, as recently shown by Gärtner et al, they can be determined analytically in terms of transversality conditions (Gärtner et al, 2019).…”
Section: Bifurcation Structure Of the Periodic Turing Patternsmentioning
confidence: 88%
“…For ε = 0 there is a plethora of non-trivial (non-constant) stationary solutions, cf. [8,21]. We start with such a solution under the assumption of its nondegeneracy according to the following definition.…”
Section: Resultsmentioning
confidence: 99%
“…Existence and bifurcation behavior of solutions of (1.1) have been studied quite well, cf. [8,9,12,13,21,23,24,25,26] and their stability properties have been investigated in [3,4,14,15,16,28,30]. Analytical and numerical investigations of (1.2) have recently been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However recent, studies showed that it is possible to reach the values of 20-40% 16,17 even without any special schemes, showing that this problem has not been fully investigated and no fundamental limit of the conversion efficiency has been clearly defined. Although previous studies concerned the dependence of the pump conversion efficiency on the Free Spectral Range (FSR) of the microresonator, 17 the input power and the coupling rate, 18,19 those dependencies were usually treated independently and only general trends were shown. In reality both FSR and coupling influence the threshold power -the former through the mode volume, and the latter through the loaded quality factor.…”
Section: Introductionmentioning
confidence: 99%